MiR‐330 suppresses EMT and induces apoptosis by downregulating HMGA2 in human colorectal cancer. Issue 2 (26th June 2019) - Mansoori, Behzad; Mohammadi, Ali; Naghizadeh, Sanaz; Gjerstorff, Morten; Shanehbandi, Dariush; Shirjang, Solmaz; Najafi, Souzan; Holmskov, Uffe; Khaze, Vahid; Duijf, Pascal H.G.; Baradaran, Behzad
Abstract: MicroRNAs (miRNAs) are important molecular regulatorsof cellular signaling and behavior. They alter gene expression by targeting messenger RNAs, including those encoding transcriptional regulators, such as HMGA2. While HMGA2 is oncogenic in various tumors, miRNAs may be oncogenic or tumor suppressive. Here, we investigate the expression of HMGA2 and the miRNA miR‐330 in a patient with colorectal cancer (CRC) samples and their effects on oncogenic cellular phenotypes. We found that HMGA2 expression is increased and miR‐330 expression is decreased in CRCs and each predicts poor long‐term patient survival. Stably increased miR‐330 expression in human colorectal cancer cells (HCT116) and SW480 CRC cell lines downregulate the oncogenic expression of HMGA2, a predicted miR‐330 target. Additionally, this promotes apoptosis and decreases cell migration and viability. Consistently, it also decreases protein‐level expression of markers for epithelial‐to‐mesenchymal‐transition (Snail‐1, E‐cadherin, and Vascular endothelial growth factor receptors) and transforming growth factor β signaling (SMAD3), as well as phospho‐ Protein kinase B (AKT) and phospho‐STAT3 levels. We conclude that miR‐330 acts as a tumor suppressor miRNA in CRC by suppressing HMGA2 expression and reducing cell survival, proliferation, and migration. Thus, we identify miR‐330 as a promising candidate for miRNA replacement therapy for patients with CRC. Abstract : In this study, we show that increasing miR‐330 expression in colorectal cancer (CRC) cells induces apoptosis and suppresses cell viability and migration. We also show that miR‐330 suppresses HMGA2 expression and leads to constitutively suppressed Smad3, vascular endothelial growth factor receptors (VEGFR), Snail‐1, p‐AKT, and p‐STAT3 and increase E‐cadherin proteins level in CRC cells. Altogether, these results specify that miR‐330 could be as a TS‐miRNA in CRC.